El doble filo del especismo: subhumanos y superhumanos. algunas asimetrías en filosofía liberal contemporánea - Suarez, Pablo (2020)
This article aims to study some complex issues debated in ethics, political philosophy and philosophy of law in order to identify certain asymmetries and inconsistencies in these areas when contemporary liberal philosophy deals with the moral consideration owed to animals. I will try to show how the stances adopted regarding some matters should lead to certain positions in others that refer to the moral status of animals, but that this not always is the case. This will allow me to suggest that the theoretical reasoning in those fields does not always meet with the standards of rationality, impartiality and universality that should provide its grounds, and is divided in watertight compartments that prevent to submit it to certain tests of coherence